Relationship of Postprandial Nonesterified Fatty Acids, Adipokines, and Insulin Across Gender in Human Immunodeficiency Virus–Positive Patients Undergoing Highly Active Antiretroviral Therapy - Lu, Guijing (Mary Ann Liebert, Inc., 2009)
BACKGROUND: Metabolic derangements are common in human immunodeficiency virus (HIV)-positive subjects undergoing antiretroviral therapy, but little is known about postprandial conditions. METHODS: We investigated the relationship between leptin, adiponectin, nonesterified fatty acids (NEFA), and insulin in response to a day-long meal pattern and evaluated gender differences in HIV-positive men (n = 12) and women (n = 13) undergoing highly active antiretroviral therapy (HAART). RESULTS: For both men and women, a significant decrease in postprandial NEFA levels was observed following breakfast (0.53 vs. 0.22 mmol/L, P < 0.001, baseline and at 3 hours, respectively), whereas day-long postprandial leptin and adiponectin levels showed small nonsignificant oscillations. In contrast to NEFA and adiponectin, postprandial leptin levels were significantly higher among women compared to men (P < 0.05). Postprandial NEFA levels correlated positively with fasting insulin levels (r(2) = 0.25, P = 0.016), and the postbreakfast decrease in NEFA levels correlated significantly with the postbreakfast increase in insulin levels (r(2) = 0.17, P = 0.038). No significant association between postprandial adipokines and insulin was observed. CONCLUSIONS: In HAART-treated, HIV-infected men and women, levels of NEFA, but not adipokines, showed significant postprandial variation. Furthermore, food intake resulted in significant NEFA suppression in proportion to the food-stimulated insulin increase.